A Lack of Exposure to School Psychology Within Undergraduate Psychology Coursework. (July 2019) - Bocanegra, Joel O.; Gubi, Aaron A.; Callan, Gregory L.; Grapin, Sally L.; McCall, John
School psychology is experiencing a personnel shortage crisis, and scholars suggest that a possible contributing factor is its underrepresentation in undergraduate psychology curricula. Most school psychology trainers do not teach at the undergraduate level, thus undergraduate psychology students may not be adequately exposed to school psychology during undergraduate training. Research suggests that increased knowledge and exposure to school psychology are associated with increased intentions for school psychology. In the current study, 55 undergraduate students completed measures of knowledge, exposure, self-efficacy, outcome expectations, and choice intentions at the beginning and end of professional psychology courses. Results indicated that students enrolled in undergraduate psychology courses did not demonstrate significant increases in the aforementioned areas for school psychology. Efforts such as creating school psychology–specific courses or infusing material should be made to increase the representation of school psychology in undergraduate psychology curricula.